Representasi Social Engineering Dalam Tindak Kejahatan Dunia Maya (Analisis Semiotika Pada Film Firewall) - Imas Rahmadhtul Hidayah (Universitas Wijaya Kusuma Surabaya, 2020)
In the current technological era, information is represented as a valuable asset for every individual or organization. There are three important components in information security such as ; (1) human; (2) process; and (3) technology. For perpetrators of cybercrime will look for gaps in the three components, not infrequently the human component becomes the target. From the above problems, researchers are interested in conducting studies by placing the film Firewall as research objects. The film is interesting because it's one of the action-thriller films with a cybercrime theme in banking. Through the film, researchers will examine the related representation of social engineering in cybercrime using the semiotic analysis method developed by Roland Barthes. The results show that social engineering representation is reflected in reverse social engineering based on social interaction. The implicit meaning in the Firewall film that is protecting company information must pay attention to the three components above because attacks from the inside are just as dangerous from outside attacks. Keywords: Social Engineering, Cyber World, Film